THE RELATIONSHIP BETWEEN LEARNING INTEREST AND HOME STUDY FACILITIES WITH MATHEMATICS LEARNING OUTCOMES OF STUDENT GRADE VIII - Ramadhani Nurul Hidayati; Sumargiyani Sumargiyani (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
The result of a student's mathematics learning is related to many factors. Learning interest and home study facilities are some of the factors that allegedly relate to learning outcomes. This study aims to determine whether there is a positive and significant relationship between the interest of learning and home study facilities with the results of learning mathematics students of class VIII State Junior High School (SMP Negeri) 2 Pandak Bantul District Even Semester Year Teaching 2017/2018. This type of research is classified as quantitative research. This study's population is all students of class VIII SMP Negeri 2 Pandak Bantul District, even semester 2017/2018 academic year consisting of 5 classes with 155 students. Samples were taken by random sampling technique to the class and obtained class VIII A, consisting of 31 students. Data collection techniques used questionnaires and test techniques. Test the research instrument using validity test, reliability test, and different power test. The prerequisite analysis test includes the normality test, independent test, and linearity test. Data analysis using correlation analysis and linear regression analysis. The results showed that there was a positive and significant correlation between learning interest (X1) and home study facility (X2) with mathematics learning result with Fcount = 3,6046 Â > Â Ftable = 3,34 is with R = 0,4525 and R2 = 0.2048 with Y = 15,4039 + 0,2336X1 + 0,3336X2 and (RC X1) = 31,9745%, (RC X2) = 68,0255%, (EC X1) = 6,5469%, and (EC X2) = 13.9284%.